Efectividad de la Electroestimulación sobre las disfunciones de la articulación temporomandibular: una revisión sistemática de la literatura - Balenzuela Santos, Gerson David; Flórez, Hamilton Geovani; Dallos Ojeda, Karent Juliet (Universidad Antonio Nariño, 2021)
The following project refers to a systematic review related to the use of “superficial electrostimulation in patients with TMJ dysfunction”; The scope contains analysis of the bibliography associated with the research topic from the search in different search engines, in order to demonstrate its effectiveness. With respect to what has been described, the methodology used in said review starts from the tracking of primary sources of specialized scientific articles such as Science Direct, Home - PubMed - NCBI, El, Scielo.org, among others, using and specifying keywords and inclusion criteria applied in the selection methodology. The size of the population analyzed corresponds to 33 scientific articles, of which according to inclusion criteria, they met the required parameters; The studies showed that the use of this technique is effective and recommended for the treatment of pain and other associated symptoms.